2014
DOI: 10.1111/dmcn.12619
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension of spoken language in non‐speaking children with severe cerebral palsy: an explorative study on associations with motor type and disabilities

Abstract: AIM To assess spoken language comprehension in non-speaking children with severe cerebral palsy (CP) and to explore possible associations with motor type and disability.METHOD Eighty-seven non-speaking children (44 males, 43 females, mean age 6y 8mo, SD 2y 1mo) with spastic (54%) or dyskinetic (46%) CP (Gross Motor Function Classification System [GMFCS] levels IV [39%] and V [61%]) underwent spoken language comprehension assessment with the computer-based instrument for low motor language testing (C-BiLLT), a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
64
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 34 publications
1
64
2
1
Order By: Relevance
“…This may be because their conversational partners adapt their message to an appropriate level. Also, a discrepancy may be present between understanding spoken language and what individuals are able to communicate as understood . Lastly, individuals with intellectual disability in GMFCS levels I to IV perform relatively well in interrelationships (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because their conversational partners adapt their message to an appropriate level. Also, a discrepancy may be present between understanding spoken language and what individuals are able to communicate as understood . Lastly, individuals with intellectual disability in GMFCS levels I to IV perform relatively well in interrelationships (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Studies generally suggest that non‐speaking children with severe motor impairment, regardless of type of motor disorder, have delayed language comprehension. Within motor involvement type, children with spastic CP tended to have language comprehension deficits that were more severe and generally below age expectations relative to language comprehension in children with dyskinetic CP . In addition, receptive communication growth trajectories seem to be more favorable for children with CP without intellectual disabilities .…”
mentioning
confidence: 91%
“…As mentioned above, cognition and not GMFCS level was independently associated with language impairment; other studies have found that both GMFCS and cognition were independently associated with communication . Another study highlights the importance of taking not only GMFCS level into account but also type of CP . Receptive language (i.e.…”
mentioning
confidence: 88%